Implementasi Teknik Mail Merge Sebagai Solusi Otomatisasi Surat Undangan Dan Pemberitahuan Pada Kegiatan Dasa Wisma (DAWIS) Rw 03 - Win Kurniadi; Bambang Wijonarko; Anjas Ramadhani; Tri Santoso (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of digital technology has changed the way people interact and manage their daily activities, demanding the adoption of automation solutions to increase efficiency. One of the challenges often faced is the time-consuming process of administrative correspondence. Mail Merge technology presents a superior solution that allows for the creation of mass letters quickly and accurately, reducing the burden of manual work. The Dasa Wisma Group (DAWIS) RW 03, as an organization active in community activities, is currently experiencing obstacles in the efficiency of creating invitation letters and notifications. Therefore, this community service activity is proposed to implement Mail Merge training and mentoring, which will be a practical and sustainable solution to automate the correspondence process in DAWIS RW 03.